CHARACTERIZATION OF CAROTENOID PIGMENTS FROM BACTERIAL SYMBIONTS OF SEAGRASS Thalassia hemprichii - Sri Achadi Nugraheni; Miftahuddin M Khoeri; Lia Kusmita; Yustin Widyastuti; Ocky Karna Radjasa (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Carotenoids are pigments that can be used in various applications including cosmetics and precursor ofvitamins A. Carotenoids are mostly found in higher plant leaves, fruit, and bacteria. Marine bacteriaassociated with seagrass Thalassia hemprichii collected from Menjangan Kecil Waters, KarimunjawaIslands were screened to produce the pigment and has allowed the use of these microrganism as anenvironmental friendly alternative source of new natural pigment. The isolation of bacterial symbionts onZobell 2216E medium from seagrass Thalassia hemprichii resulted in 20 isolates of which 8 bacterialsymbionts have produced pigments but only one bacterium positively synthesize carotenoids. Initial analysiswith atomic absorption spectrophotometric method revealed that the wave lengt of bacterial pigment were inthe range of 300-600 nm, which are categorized that within the group of carotenoid pigments. From theresults of molecular identification by 16S rDNA method, it was shown that bacterium TH8 was closelyrelated to Bacillus licheniformis with 98% homology value.